ENTREPRENEURS’ SOCIAL AND HUMAN CAPITAL ON THEIR KNOWLEDGE OF FINANCE ALTERNATIVES: EVIDENCE FROM INDONESIA - Pangeran, Perminas (European Scientific Journal, ESJ, 2015)
This study aims to examine the impact of entrepreneurs’ social capital and human capital on their knowledge of finance alternatives. The study was conducted through a questionnaire survey of 90 entrepreneurs (employers) of creative businesses located in Yogyakarta, Indonesia. This study found several important things. First, entrepreneurs’ social capital had a positive influence on their knowledge of finance alternatives. Second, entrepreneurs’ general human capital, only a few indicators, affected their knowledge of finance alternatives. These results showed weak support for the influence of general human capital on the knowledge of finance alternatives. Third, interestingly, entrepreneurs’ specific human capital had no impact on their knowledge of advanced finance alternatives for the growth phase. These results also provided weak support for the influence of specific human capital on the knowledge of finance alternatives.